Temporal trends in tuberculosis and time from enrolment in care to antiretroviral therapy initiation: A multicountry cohort study from Latin America - Bryan E Shepherd; Zhuohui Liang; Ahra Kim; Carina Cesar; Valdilea G. Veloso; Claudia P. Cortes; Marco T. Luque; Brenda Crabtree-Ramirez; Eduardo Gotuzzo; Karu Jayathilake; Jessica L. Castilho; Jean W. Pape; et al. (International Journal of Infectious Diseases, 2025)
ABSTRACT: Background: HIV treatment guidelines have evolved to recommend rapid antiretroviral therapy (ART) initiation. Data on the impact of these changes in the Americas region are scarce. Methods: This study included data from CCASAnet sites in Brazil, Haiti, Honduras, Mexico, and Peru. ART-naïve adults who started ART from 2006 to 2022 were included. Trends in CD4 count, tuberculosis (TB), and treatment initiation were described using cumulative probability and logistic and Cox regression models. Findings: Total 29,881 PLWH met inclusion criteria; 2179 (7.3%) were diagnosed with prevalent TB and 379 (1.2%) with incident TB within six months after ART initiation. For individuals without TB, enrolment CD4 count increased from 160 to 320 cells/mm3. Over the study period, TB prevalence declined from peak of 9.4% to 5.4%, and incident TB from 1.5% to 0.8%. Median time to ART initiation decreased from 476 to 1 day for PLWH without TB, and 98 to 16 days for those with prevalent TB; time to TB treatment also decreased. Conclusions: Time to ART initiation has decreased in the CCASAnet consortium, with the majority of PLWH now starting ART within a week after enrolment. There has also been a decline in the prevalence and incidence of concurrent TB disease.